Rapid Response to Penpulimab Combined With Anlotinib and Chemotherapy in a Thoracic SMARCA4‐UT Without PD‐L1 Expression: A Case Report and Review of Literature - Yuanhang Wang; Kelei Zhao; Jingjing Zhang; Xiaohan Yuan; Yanting Liu; Jinghang Zhang; Ping Lu; Min Zhang (The Clinical Respiratory Journal)
ABSTRACT SMARCA4‐deficient undifferentiated tumor (SMARCA4‐UT) in the chest is a high‐grade malignant tumor that grows rapidly and often carries a poor prognosis. Unfortunately, there are currently no effective treatment available until now. Here, we report a case of SMARCA4‐UT in a patient who showed a swift response to a combination treatment of penpulimab, anlotinib, and chemotherapy. A 55‐year‐old man was diagnosed with thoracic SMARCA4‐UT along with metastases to multiple lymph nodes, the pleura, and bones. Immunohistochemical (IHC) testing indicated the absence of PD‐L1 expression in tumor cells. He was given sintilimab and anlotinib as first line treatment. However, a follow‐up chest CT revealed progressive disease (PD) after the first cycle treatment. Subsequently, the second line regimen was modified to etoposide and cisplatin (EP) combined with anlotinib and penpulimab. The effectiveness evaluation revealed partial remission (PR) following two cycles of the second‐line regimen treatment. Notably, the patient's progress‐free survival (PFS) exceeds 7 months and the overall survival up to 12 months. Our case implies that a combination of chemotherapy, anlotinib, and penpulimab might offer a promising therapeutic approach for PD‐L1‐negative thoracic SMARCA4‐UT.